Ebola Virus Disease and Epidemic Development in the West-African Countries in 2014 (Review) - Yu. I. Arutyunov; E. A. Moskvitina; T. V. Kovaleva (Проблемы особо опасных инфекций, 2015)
The review presents the data on the development of epidemic caused by Ebola virus in the West-African countries - Liberia, Sierra Leone, Nigeria, Senegal, and Mali. Analyzed is also an epidemic in the Democratic Republic of the Congo, unrelated to the mentioned above outbreaks. Traced have been the chains of transmission and import of the disease (under control and out-of-control) into European and American states. Assessed are the premises for complications faced in the course of epidemic response, and the factors contributing to the wide spread of the infection.